AKTIVITAS ANTIJAMUR MINYAK ATSIRI RIMPANG DRINGO (Acorus calamus L.) TERHADAP JAMUR Botryodiplodia theobromae PENYEBAB BUSUK BUAH PISANG - Rustini, N. L. (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 2 Juli 2010, 2012)
A compound with antifungal activity has been isolated from dringo (Acorus calamus L.) essential oil. Steam distillation was conducted to isolate the oil and resulted in 0.5 % yield. Antifungal activity test towards Botryodiplodia theobromae showed that the ethanol posseses antifungal activity with an inhibition capacity of 94.4 %. GC-MS analysis resulted in three main peaks at 15.008; 15.233; and 16.490 minutes. It was suggested from the peak intensity that the last peak represents the major component of the extract. Futher more according to the library data base, the spectra of this compound matches with the Asarone spectra.
Keywords: Antifungal, Dringo, Botryodiplodia theobroma